Practical Pediatric Gastrointestinal Endoscopy. - Gershman, George; Thomson, Mike. (Hoboken : John Wiley & Sons, 2011)
This practical step-by-step guide to performing GI endoscopy safely and effectively in children covers the use of endoscopy as both a diagnostic and a therapeutic modality. Now with an entirely new section focusing on advanced endoscopic techniques, such as such as pancreatic cysto-gastrostomy, confocal endo microscopy, and single balloon enteroscopy, the new edition gives trainees and practitioners access to the most recent, as well as the most dependable, information.
10: Endoscopic hemostasis of variceal bleeding with polymeric glue: indications, preparation, instruments and technique and complications of N-butyl-2-cyanoacrylate injectionPreparation and technique; Complications; Thrombin; FURTHER READING; 11: Endoscopic treatment of benign esophageal strictures with removable or biodegradable stents; Introduction; Conventional treatment of esophageal strictures in children; Esophageal stent: the new approach to refractory or relapsing benign esophageal strictures; Pediatric experience; Discussion and conclusion; FURTHER READING.
12: Endoscopic application of Mitomycin C for intractable strictures.
Print version record.
Keywords: Pediatric gastroenterology; Gastrointestinal system -- Endoscopic surgery; Endoscopy, Gastrointestinal; Gastroenterology -- Endoscopic surgery; Medical -- Pediatrics; Pediatric gastroenterology -- Endoscopic surgery; Pediatrics -- Methods; Medicine; Electronic books